Probing Quantum Confinement and Electronic Structure at Polar Oxide Interfaces. Issue 8 (24th June 2018) - Li, Danfeng; Lemal, Sébastien; Gariglio, Stefano; Wu, Zhenping; Fête, Alexandre; Boselli, Margherita; Ghosez, Philippe; Triscone, Jean‐Marc
Abstract: Polar discontinuities occurring at interfaces between two materials constitute both a challenge and an opportunity in the study and application of a variety of devices. In order to cure the large electric field occurring in such structures, a reconfiguration of the charge landscape sets in at the interface via chemical modifications, adsorbates, or charge transfer. In the latter case, one may expect a local electronic doping of one material: one example is the two‐dimensional electron liquid (2DEL) appearing in SrTiO3 once covered by a polar LaAlO3 layer. Here, it is shown that tuning the formal polarization of a (La, Al)1− x (Sr, Ti) x O3 (LASTO: x ) overlayer modifies the quantum confinement of the 2DEL in SrTiO3 and its electronic band structure. The analysis of the behavior in magnetic field of superconducting field‐effect devices reveals, in agreement with ab initio calculations and self‐consistent Poisson–Schrödinger modeling, that quantum confinement and energy splitting between electronic bands of different symmetries strongly depend on the interface total charge densities. These results strongly support the polar discontinuity mechanisms with a full charge transfer to explain the origin of the 2DEL at the celebrated LaAlO3 /SrTiO3 interface and demonstrate an effective tool for tailoring the electronic structure at oxide interfaces. Abstract : Quantum confinement in SrTiO3 at the oxide interface depends on the overlaying polar materials. It is found that a full transfer of charges takes place at the LaAlO3 /SrTiO3 interface with the density predicted by first‐principle calculations, thus answering a long‐standing open question regarding the origin of the 2D electron liquid present at the interface.